Serum RANTES level influences the response to pegylated interferon and ribavirin therapy in chronic hepatitis C. Issue 8 (28th December 2012) - Komase, Kazuki; Maekawa, Shinya; Miura, Mika; Sueki, Ryota; Kadokura, Makoto; Shindo, Hiroko; Shindo, Kuniaki; Amemiya, Fumitake; Nakayama, Yasuhiro; Inoue, Taisuke; Sakamoto, Minoru; Yamashita, Atsuya; et al.
<x xml:space="preserve">Abstract</x> Aim Prediction of treatment responses to pegylated interferon (PEG IFN) plus ribavirin (RBV) therapy is uncertain for genotype 1b chronic hepatitis C. Methods In this study, 96 patients were investigated for the correlation between 36 pretreatment serum chemokine/cytokine levels and PEG IFN/RBV treatment efficacy by a sandwich enzyme‐linked immunoassay (ELISA) and a bead array. Results First, chemokines/cytokines were measured semiquantitatively by sandwich ELISA in 31 randomly‐selected patients and the serum regulated on activation normal T‐cell expressed and secreted (RANTES) level was found to be significantly higher in the sustained virological response (SVR) group than the non‐SVR group (P = 0.048). Precise RANTES measurement in all 96 patients using a bead array confirmed this correlation (P = 0.002). However, the genetic RANTES haplotype was not significantly related to the serum level. The serum RANTES level was extracted by multivariate analysis (odds ratio = 4.09, 95% confidence interval = 1.02–16.5, P = 0.048) as an independent variable contributing to SVR. Conclusion The serum RANTES level is an important determinant influencing the virological response to PEG IFN/RBV therapy in chronic hepatitis C.